Effects of probiotic supplementation on related side effects after chemoradiotherapy in cancer patients - Lu, Yongkai; Luo, Xiaoqin; Yang, Di; Li, Yi; Gong, Tuotuo; Li, Binglin; Cheng, Jian; Chen, Ruijuan; Guo, Xin; Yuan, Wei (Frontiers in Oncology, 2022)
Objectives Chemotherapy and radiotherapy generally cause serious adverse side effects in cancer patients, thereby affecting subsequent treatment. Numerous studies have shown that taking probiotics is an option for preventing and treating these side effects. This study aims to perform a meta-analysis concerning the efficacy of oral probiotics on adverse events induced during radiotherapy, chemotherapy, or chemoradiotherapy treatment. Results Sixteen randomized controlled trials including 2,097 patients were extracted and analyzed by standard meta-analysis procedures. Compared with the placebo groups, oral probiotics significantly reduced the side effects caused by radiotherapy and chemotherapy on various types of cancer, such as head and neck cancer, pelvic and abdominal cancer, breast cancer, lung cancer, etc. (OR: 0.31, 95% CI: 0.20 – 0.48; P < 0.005). Further analysis found that the incidence of diarrhea in patients with pelvic and abdominal cancers (OR: 0.32, 95% CI: 0.16 - 0.65; P < 0.005) and the frequency of oral mucositis in patients with head and neck tumors were also significantly lower (OR: 0.28, 95% CI: 0.18 - 0.43; P < 0.005) after the oral administration of probiotics. This suggests that probiotics have a positive influence on the treatment of side effects after chemoradiotherapy. Furthermore, a funnel plot suggested that this study had no significant publication bias. Conclusions Probiotics may reduce the incidence of cancer therapy-induced side effects, especially oral mucositis in head and neck tumors and diarrhea in patients with pelvic and abdominal tumors. However, considering the small number of clinical trials involved, further randomized, double-blind, multicentric trials in a larger population are required. This paper may help researchers to improve trial design in the selection of probiotic strains and choose suitable patients that may benefit from probiotic treatments.